Job satisfaction among non-managerial employee in Southernhem Industries Sdn Bhd Demak Laut Industrial Park / Priscilla Diau - Diau, Priscilla (2015)
The purpose of this study is to identify the impact of physical, psychological and environmental factor towards non-managerial employee job satisfaction. This research was to determine the most important factor that affect to the employee job satisfaction and also to recommend on how to improve employee job satisfaction. The study was used a questionnaire to gain the gain the result related to employee job satisfaction. 103 of the questionnaires has been distributed as the population size was 140 employees. Data collected has been analysis by using SPSS software (Statistical Software Package). From the result, it shows that physical, psychological and environmental factors are affected to the job satisfaction of nonmanagerial employee of Southernhem Industries Sdn Bhd but strongly affected to their job satisfaction. This because according to the each factors values of correlation coefficient is weak. Generally, the study implies that the Southernhem Industries Sdn Bhd management should improve on their management system so that their employee would more satisfied and love to work there.